Iodine Fortification on Brown Sugar : The Effect of Fortification Period and Source of Iodine - Rifda Naufalin; Budi Sustriawan; Poppy Arsil (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
Gula kelapa is a traditional and potencial comodity in Banyumas. Fortification with iodium in gula kelapa should be criteria were iodium in product over than 30 ppm bk. Fortification process was need a long thermal process. Stability of iodium in gula kelapa has been studied. The experimental method used Randomized Block Design. The factors analyzed were three kinds of fortification (fresh nira, nira prosessed, nira cristalization) and four kinds of iodium (control, NaI, KI, and KIO3) with 3 replications, and total were 36 unit. The result of the research showed that fortification when nira after endpoint with kalium iodida is the best interaction, iodium content is 34,89 ppm db. Key words : Brown sugar, fortification, iodine.